Enhancement of work habits and behavior of persons with mental retardation through paper craft making - Umali, Aileen M. (2008)
This study aimed to determine the present work performance level of Persons with Mental Retardation (PMR) and the effect of the work program in papercraft-making on their work habits and behavior. Ten students with mild and moderate mental retardation and had preexisting skills in papercraft were the subjects of the study. A one-group pretest-posttest experimental research method, among other qualitative methods, was utilized to gather data for the study. These were assessed using Work Habits and Behaviors Rating Scale. It was found that there was marked improvement in PMR in terms of the following: attendance, working with others, accepting supervision, working at a satisfactory production rate, and meeting demands for quality work. The severity of mental retardation affects the students' skills in working at a satisfactory production rate and meeting the demands for quality work.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: People with mental disabilities -- Education -- Philippines -- Laguna; People with mental disabilities -- Philippines -- Laguna -- Attitudes; Special education -- Philippines -- Laguna; Paper work; People with mental disabilities -- Behavior modification -- Philippines -- Laguna